IMPLEMENTASI TEORI HUKUM PROGRESIF DALAM PENEMUAN HUKUM OLEH HAKIM NIAGA STUDI KASUS KEPAILITAN PT. SRI REJEKI ISMAN TBK (SRITEX) - Bella Intan Feronica; Irwan Triadi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This research examines the application of progressive legal theory in judicial legal discovery by commercial court judges through a case study of the bankruptcy of PT Sri Rejeki Isman Tbk (Sritex). The study employs a normative juridical method by analyzing legal doctrines and the ratio decidendi of the decision. The results show that (1) legal discovery is required in issues of simple proof, debt verification, stay period, and the rights of secured creditors. (2) judges apply systematic and teleological interpretation to balance certainty, justice, and utility. (3) the absence of adoption of the UNCITRAL Model Law necessitates cross-border legal construction. It concludes that progressive law effectively prevents rigid formalism and promotes substantive justice. Recommendations: reinterpretation of “simple proof,” protection of weaker parties, and cross-border harmonization.